E-Tester: A computer-based tool for auto-generated question and answer assessment - Dreher, Heinz; Williams, Robert; Guetl, C. (Association for the Advancement of Computing in Education, 2005)
Adaptive E-Learning systems are needed to efficiently support lifelong learning activities. To check goal attainment, learners need to take tests or assessment activities. Large efficiency gains may be made if the assessment and associated grading or evaluation process could be supported with adaptive systems sensitive to user parameters. Hand made tests are a time consuming and tiresome task. If the tests are hand scored there is the inevitability of either interrupting the learning whilst the assessment outcome is pending, or the danger of proceeding with the attempt at learning possibly unsuitable content. As a contribution to solving the problem stated so far we have designed the E-TESTER. In this paper we describe the implementation solution and its integration into the AdeLE system, point out the potential of the E-TESTER by an application example, and discuss the experiences of the prototype implementation.